2010
DOI: 10.1159/000314305
|View full text |Cite
|
Sign up to set email alerts
|

Sixty Years of Lithium Responders

Abstract: It has been 60 years since Cade first described patients who responded to antimanic lithium treatment. Two decades later, responders to lithium stabilization emerged in larger numbers. The responses of many severely ill bipolar patients to lithium were striking and called for an explanation. Remarkable reactions to a simple ion generated hope for an uncomplicated laboratory test of response and an extensive search for suitable biological markers ensued. But despite promising reports, particularly from molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 109 publications
3
62
0
8
Order By: Relevance
“…One of the lightest metallic elements had a heavy impact on the concepts and practice of modern psychiatry. Some scientific studies on lithium and clinical experience collected during recent decades partly confirmed early anecdotal findings, and partly remodeled and integrated them into updated, more precise and comprehensive concepts, thus making previous observations better understood [1,2] . Other studies detected or redetected important aspects of lithium which either are still to be discussed on a hypothetical level such as its 'neuroprotective' effects, or which are supported by very good scientific evidence but still did not find their way into everyday clinical practice and existing guidelines.…”
Section: Introductionmentioning
confidence: 87%
“…One of the lightest metallic elements had a heavy impact on the concepts and practice of modern psychiatry. Some scientific studies on lithium and clinical experience collected during recent decades partly confirmed early anecdotal findings, and partly remodeled and integrated them into updated, more precise and comprehensive concepts, thus making previous observations better understood [1,2] . Other studies detected or redetected important aspects of lithium which either are still to be discussed on a hypothetical level such as its 'neuroprotective' effects, or which are supported by very good scientific evidence but still did not find their way into everyday clinical practice and existing guidelines.…”
Section: Introductionmentioning
confidence: 87%
“…Further, the family history typically includes recurrent mood disorders, not chronic psychotic illnesses. 10,44,45 Granted there are intermediate clinical presentations and reports of overlapping genetic and neurobiological findings; however, in part this reflects the broadening of the BD concept 20,46 and assortative mating. 47,48 Another challenge to the proposal of simply generalizing the early psychosis model to mood disorders is that BD is not diagnosed until the manifestation of the first-activated (hypomanic or manic) episode; however, the classical disorder almost always starts with depressive episodes.…”
Section: 26mentioning
confidence: 99%
“…Otro aspecto es la heterogeneidad de las poblaciones clínicas, constituyendo uno de los mayores obstáculos en la obtención de resultados "limpios" y más objetivos 32 . Los posibles mecanismos de acción específicos para el litio se citan en Tabla 1.…”
Section: Teorías Sobre El Litio Y La Prevención Del Suicidiounclassified